Hand Muscle Grip Strength on Pre- And Post- Rubber Ball Performing Exercises of Older People - Pangaribuan, Isabel NA; Nugroho, Nunung; Oenarta, Dave G (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: The number of older people in Indonesia continues to rise. Aging process will cause changes in organ systems, one of which is changes in the musculoskeletal system. One of the significant weakening of function in the elderly is the degrading strength of the handheld muscles, which resulted in a decrease of functional abilities. One method which can be used to increase hand muscle grip strength is by doing rubber ball exercise. Aim: To analyze the difference of hand muscle grip strength on pre- and post- performing rubber ball exercises in elderlies at St. Joseph Nursing Home in Surabaya. Method: This study is a pre-experimental analytic research with one group pretest – posttest design approach. The sampling technique used consecutive sampling, with a total sample of 48 elderlies. The interventions for rubber ball exercises were carried out three times a week for one month. Instruments used for this study were the MMSE and MNA-SF questionnaires. The hand muscle grip strength was measured using the Handgrip Dynamometer. data analysis was done using the SPSS program and the Chi-Square test. Results: The mean total value of the muscle grip strength pre-exercises was 10,8 ± 3,9 kg. The mean total value of the hand muscle grip strength post exercises was 11,97 ± 4,08 kg. The data analysis results show that there was a significant difference between pre- and postperforming rubber ball exercises on the elderly at St. Joseph nursing home in Surabaya. (p=0,025). Conclusion: There is a significant contrast between pre and post-performing rubber ball exercises on the elderly at St. Joseph nursing home in Surabaya.